(untitled) (Research, Society and Development, 2021)
Objective: To analyze the patient safety culture in a private hospital in southern Brazil. Method: This is an exploratory, descriptive study with a quantitative approach, carried out in August and September 2019 through the Safety Attitudes Questionnaire. 100 workers from different professional categories participated in the three work shifts. Data analysis was performed using descriptive statistics. Results: The patient safety culture in the institution is considered adequate, since most domains presented a percentage between 50% and 75% of positivity. Conclusions: The results are considered positive, since the results are positive for most research participants, however it is necessary to invest in the qualification of health practices, mainly through the continuous and permanent education of the active multidisciplinary teams and availability of tools that help in these dynamics.